The reliability of the titan 1+ 10 Hz global positioning system for measures of distance and distance within speed zones - Elia, V.; Cappaert, T.; Neeld, K.; Harmon, M. C. (International Journal of Strength and Conditioning, 2023)
Introduction: This experiment was designed to investigate the inter and intra-unit reliability of the Titan 1+ 10 Hz global positioning system (GPS) for measures of distance and distance within speed zones during straight-line and change of direction running at varying distances and speeds, as well as during a team-sport simulated circuit.